Role of external cavity reflectivity for achieving polarization control and stabilization of vertical cavity surface emitting laser - Arizaleta Arteaga, Mikel; López-Amo, Manuel; Thienpont, Hugo; Panajotov, Krassimir (Applied physics letters, 2007)
The authors present the experimental results showing how the external mirror reflectivity affects the polarization properties of a vertical cavity surface emitting laser subject to optical feedback from an extremely short external cavity. The amplitude of modulation of the polarization switching current with the external cavity length is found to be proportional to the external mirror reflectivity, confirming its key role in achieving polarization control and stabilization of such lasers using optical feedback. Numerical simulations presented here show good agreement with experiments.